Rancang bangun Sistem Pengolahan Data Perpajakan Menggunakan Framework Code Igniter (Information Technology and Telematics, 2014)
Abstract - Taxes are our most important obligation in acountry. Lack of in order to pay taxes devastating for regionaldevelopment because the funds used are from the tax. The mainproblem in this paper is how to process the data property tax inorder to know the same is payable in full.Sidorejo Village is a thriving village which is very good activitytax payment but inside still use manual data processing. Thusthe authors tried to make a data processing system to make iteasier to process data in which the property tax payable toknow that the same is paid off.The data processing system is designed using FrameworkCodeIgniter programming language.Keywords – Tax, data processing, Framework CodeIgniter,